Causal Relationships between Current Account Imbalances and Budget Deficits in Pacific Island Countries: A Panel Cointegration Study - Jayaraman, T.K; Lau, Evan (School Of Economics University Of The South Pacific, 2008)
Resorting to panel data investigation, this study seeks to test the causal relationships between current account imbalances and budget deficits in Pacific island countries. The study findings are that current account imbalances and budget deficits are cointegrated, although there is no long run causality relationship between current account deficit and budget deficit and money supply. However, in the short run, there is a bidirectional relationship between current account deficit and budget deficit. The study suggests some policy measures.